Comparison of power output generated on the Wingate cycle ergometer and on a new, closed-chain lower-extremity dynamometer - Dolny, D. G.; Collins, M. G.; German, S. L.; Phipps, W. T.; Davis, H. R. (The Journal of Strength and Conditioning Research, 2000)
Ten trained male subjects (age range, 24 ± 3 years) performed the 30-second Wingate anaerobic cycle test (WIN) and a 30-second maximal effort test on the semirecumbent, lower-extremity Omnikinetic dynamometer (OmK). The OmK uses a bilateral, concentric, and eccentric stair-stepping motion. WIN resistance (N) was 0.90 × subject`s body weight in kilograms, whereas OmK resistance (pounds) was set at 100% of body weight. Measures of peak power (PP [W]), relative peak power (Rel-PP [W·kg1]), mean power (MP [W]), relative mean power (Rel-MP [W·kg1]), fatigue index (FI [%]), and fatigue slope (FS [W·sec1]) were calculated for each test. OmK PP and MP were the sum of the right and left crank powers. WIN PP (918 ± 35 W) and Rel-PP (12.2 ± 1.9 W·kg1 ) were greater (p < 0.05) than OmK PP (770 ± 119 W) and Rel-PP (10.1 ± 1.8 W·kg1). Mean power and Rel-MP were similar for WIN (MP = 668 ± 148 W; Rel-MP = 8.8 ± 1.7 W·kg1) and OmK (MP = 685 ± 121 W; Rel-MP = 9.1 ± 1.8 W·kg1). Pearson product moment correlations for WIN and OmK PP and for Rel-PP were 0.78 (p < 0.01) and 0.70 (p < 0.02), respectively, and were 0.84 (p < 0.01) and 0.81 (p < 0.01) for MP and Rel-MP, respectively. FI was greater (p < 0.05) for WIN (45 ± 6%) compared with OmK (26 ± 7%). These results demonstrate that MP produced on OmK is comparable to MP produced on WIN. However, the lower PP on OmK may reflect either an actual difference in PP potential between these 2 tests or a suboptimal resistance setting to elicit PP on the OmK.